Palaearctic Hoplitis bees of the subgenera Formicapis and Tkalcua (Megachilidae, Osmiini): biology, taxonomy and key to species - Müller, Andreas; Mauss, Volker (Zootaxa, 2016)
Formicapis and Tkalcua are related subgenera of the osmiine bee genus Hoplitis (Megachilidae) containing four and three species, respectively. H. (Formicapis) species inhabit open forests and windfalls mainly in the boreal zone with one species distributed across the Holarctic and three species occurring in eastern Asia. H. (Tkalcua) species live in deserts and semideserts from the Canary Island and northern Africa eastwards to the Arabian Peninsula. Analysis of female pollen loads, field observations and literature data reveal that H. (Formicapis) species have a distinct or even exclusive preference for the flowers of herbaceous Rosaceae as pollen hosts, while H. (Tkalcua) species appear to be pollen generalists. Nesting sites of H. (Formicapis) are insect burrows in dead wood, while the only H. (Tkalcua) species, whose nesting behaviour is known, builds its brood cells inside empty snail shells. Species of both subgenera construct brood cell partitions and nest plug with masticated leaves, which, however, are mixed with sand grains in H. (Tkalcua) zandeni (Teunissen & van Achterberg 1992). The taxonomic revision of H. (Formicapis) and H. (Tkalcua) revealed the existence of two undescribed species, H. (Formicapis) coreensis spec. nov. from South Korea and H. (Tkalcua) emiratensis spec. nov. from the United Arab Emirates. Hoplitis excisa (Morawitz 1880) is newly assigned to H. (Formicapis), whereas H. latifemoralis (Wu 1985), formerly considered to belong to H. (Formicapis), is removed from this subgenus due to morphological and biological differences and newly assigned to Hoplitis subgenus incertum. Identification keys for all H. (Formicapis) and H. (Tkalcua) species are given.